Charge heterogeneity of therapeutic monoclonal antibodies by different cIEF systems: views on the current situation - Alessandro Ascione; Marcello Belfiore; Jaana Vesterinen; Mihaela Buda; Wolf Holtkamp; Francesca Luciani (Taylor & Francis Group, 2024)
ABSTRACTTherapeutic mAbs show a specific "charge fingerprint" that may affect safety and efficacy, and, as such, it is often identified as a critical quality attribute (CQA). Capillary iso-electric focusing (cIEF), commonly used for the evaluation of such CQA, provides an analytical tool to investigate mAb purity and identity across the product lifecycle. Here, we discuss the results of an analysis of a panel of antibody products by conventional and whole-column imaging cIEF systems performed as part of European Pharmacopoeia activities related to development of "horizontal standards" for the quality control of monoclonal antibodies (mAbs). The study aimed at designing and verifying an independent and transversal cIEF procedure for the reliable analysis of mAbs charge variants. Despite the use of comparable experimental conditions, discrepancies in the charge profile and measured isoelectric points emerged between the two cIEF systems. These data suggest that the results are method-dependent rather than absolute, an aspect known to experts in the field and pharmaceutical industry, but not suitably documented in the literature. Critical implications from analytical and regulatory perspectives, are herein thoughtfully discussed, with a special focus on the context of market surveillance and identification of falsified medicines.